Dépendance à l’automobile, tension dans les mobilités et stratégies des ménages - Cyrille Genre-Grandpierre; Didier Josselin (Cybergeo, 2008)
General access to automobile speed has enabled the separation between the places of life, in particular between the house and the place of work. In return, people are now addicted to this speed. Without speed, it is often impossible to perform the everyday life within the limits of a fixed travel-time. With the beginning of a stagnation or even a decrease in automobile speed, the urban functioning based on speed is more and more under tension and seems to be questioned in the short term. According to this assessment, the aim of this article is, first of all, to identify using the example of the commuters to Avignon, where automobile speed dependency and tension in the mobility system are currently the highest, and thanks to GIS simulations, to see their probable evolution. In a second time, we aim to analyse the way speed dependency and tension are perceived and felt, to identify the strategies of the households to dodge this issue, in particular in terms of location choice.